Identification of Rat Testicular Leydig Precursor Cells by Single-Cell-RNA-Sequence Analysis - Guan, Xiaoju; Chen, Panpan; Ji, Minpeng; Wen, Xin; Chen, Dan; Zhao, Xingyi; Huang, Fu; Wang, Jiexia; Shao, Jingjing; Xie, Jiajia; Zhao, Xingxing; Chen, Fenfen; et al. (Frontiers in Cell and Developmental Biology, 2022)
Stem Leydig cells (SLCs) play a critical role in the development and maintenance of the adult Leydig cell (ALC) population. The identification, characteristics, and regulation of SLCs in the adult testis remain uncertain. Using single-cell RNA-seq, we found that the mesenchymal stromal population may be involved in ALC regeneration. Upon ALC elimination, a fraction of stromal cells begins to proliferate while a different fraction of the population begins to differentiate to ALCs. Transcriptomic analysis identified 5 stromal clusters that can be classified into 2 major groups representing proliferation and differentiation populations. The proliferating group represents stem cells expressing high levels of CD90, Nes, Lum, Fn and Gap43. The differentiating group represents a progenitor stage that is ready to form ALCs, and specifically expresses Vtn, Rasl11a, Id1 and Egr2. The observation that the actively dividing cells after ALC loss were not those that formed ALCs suggests that stem cell proliferation and differentiation are regulated separately, and that the maintenance of the stromal stem cell pool occurs at the population level. The study also identified specific markers for the major interstitial cell groups and potential paracrine factors involved in the regulation of SLCs. In summary, our data suggest a new theory about SLC identity, proliferation, differentiation, and regulation.